2007
DOI: 10.1088/0031-9155/52/12/012
|View full text |Cite
|
Sign up to set email alerts
|

Phase and amplitude binning for 4D-CT imaging

Abstract: We compare the consistency and accuracy of two image binning approaches used in 4D-CT imaging. One approach, phase binning (PB), assigns each breathing cycle 2pi rad, within which the images are grouped. In amplitude binning (AB), the images are assigned bins according to the breathing signal's full amplitude. To quantitate both approaches we used a NEMA NU2-2001 IEC phantom oscillating in the axial direction and at random frequencies and amplitudes, approximately simulating a patient's breathing. 4D-CT images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 24 publications
4
114
0
Order By: Relevance
“…Abdelnour et al 49 shows that amplitude binning can be more accurate than phase binning when using 4DCT imaging. Moreover, for irregular target trajectories, phase binning can lead to large reconstruction errors that need to be addressed using complex iterative techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Abdelnour et al 49 shows that amplitude binning can be more accurate than phase binning when using 4DCT imaging. Moreover, for irregular target trajectories, phase binning can lead to large reconstruction errors that need to be addressed using complex iterative techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These mismatches become visible as artifacts in reconstructed 4D CT images. [1][2][3][4][5][6][7][8] These artifacts appear as undefined or irregular boundaries in the 4D CT images and cause systematic errors in patient contouring and dose calculations. Various studies have shown that the magnitude of artifacts resulting from retrospective displacement sorting is less severe than those resulting from retrospective phase sorting.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that the magnitude of artifacts resulting from retrospective displacement sorting is less severe than those resulting from retrospective phase sorting. 1,3,5,7 Recently it was found that at least one artifact appeared in retrospectively phase sorted 4D CT images for 45 out of 50 patients. 9 The problem with retrospective displacement sorting is, on the other hand, that data may be insufficient at some couch positions because of variations in the respiratory motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of 4D CT imaging (3-dimensional CT volumes plus time), the robustness of this phase model was unreliable in the case of irregular breathing (3). Alternative approaches accounting for irregular breathing cycles have been proposed, such as adaptive phase binning accounting for the length of individual cycles or, alternatively, the use of respiration amplitude binning (4).…”
mentioning
confidence: 99%